“Living with Illegal Feelings”—Analysis of the Internet Discourse on Negative Emotions towards Children and Motherhood - Garncarek, Emilia (Qualitative Sociology Review, 2020)
The aim of the article is to show the socio-cultural conditions influencing the ways of expressing emotions and feelings by mothers. It presents the results of the analysis of the Internet discourse on negative attitudes towards motherhood and/or a child/children. The text is built on the author’s research on the issue of “regretting motherhood” and is based on a qualitative analysis of the content—blog entries/posts: nieperfekcyjnie.pl [notperfect.pl], matkawygodna.pl [slackermom.pl], mamwatpliwosc.pl [ihaveadoubt.pl], and in the group—Internet forum—Żałuję rodzicielstwa [I regret parenthood]. The theoretical basis were the concepts included in the sociology of symbolic interactionism.